Design and optimization of thin film organic solar cells - Ng, Ging Meng (2009)
The aim of this Ph.D. project was to undertake a systematic study to develop a technique for improving the performance of solution-processed translucent P3HT:PCBM-based solar cells over the two competing indexes: power conversion efficiency and transmittance, for stacking up or transparency. A comprehensive optical admittance analysis was applied to study the optical properties of conventional opaque and translucent P3HT:PCBM-based PSCs. The simulation uses the dispersive refractive index n(λ) and extinction coefficient k(λ) of P3HT:PCBM blend and other functional layers that were measured by VASE to calculate the optical absorbance and transmittance of P3HT:PCBM-based PSCs. The optimal device structure was obtained by maximizing the light absorption of the active layer (P3HT:PCBM) and the transmission of the whole translucent PSCs. AFM was used to examine the surface roughness of the P3HT:PCBM film prepared in this work. Based on the optimal device parameters derived from the simulation, a 60 nm thick ITO was found to be optimal and was used to fabricate the translucent PSCs with the structure of glass/ITO/PEDOT:PSS/P3HT:PCBM(75nm)/Ca(10nm)/ Ag(10nm)/ITO(60 nm).